Mosques, Muslims, Methods: the Role of Mosques in Research about Muslims in Europe - Brekke, Torkel (Journal of Muslims in Europe, 2019)
Previous research has questioned the use of mosques as points of entry for research about Muslims in Europe. Part of the background has been a new emphasis on lived religion and a critique of a one-sided focus on religious institutions. We argue that some of this criticism is theoretically ill-founded and we also point out that some trends may make mosques more important in research about Muslims. In section 1, we go through the most important literature addressing the methodological problems posed by using mosques in research about Muslims in the West. In section 2, we look at some of the fundamental problems of definitions in some of this critical methodological literature. In section 3, we discuss how the choice of methods, not least sampling modes, will be of significance for meaningful discussion about the appropriateness of using mosques in research, and in section 4, we present what we see as important advantages of using mosques as a point of entry to study Muslims. In section 5, we conclude with a brief summary and discussion.